Application of Dextroscope in a Rare Type of Angiomatous Meningioma Characterized With Coral-Like Vessels. Issue 4 (June 2019) - Ma, Shun-Chang; Yang, Jun; Jia, Wang
Abstract : Abstract: A 43-year-old female diagnosed with meningioma was admitted to our department. Preoperative imaging revealed a spherical lesion located in the sphenoid ridge with obvious enhancement and inhomogeneous density into 3 layers on magnetic resonance (MR) images, coral-like vessel images inside the tumor was obtained after the raw computed tomography angiography data were imported into the Dextroscope virtual-reality system. Due to her progressive headache and visual deterioration, surgery was performed after comprehensive study in the Dextroscope system, details about the correlation among skull base, lesion, branches of internal carotid artery, and vessels inside the tumor were well demonstrated in this system. It is diagnosed as a rare type of angiomatous meningioma, based on the abnormal manifestation on images, which even make it important to make further evaluation before making any surgical plan. Surgical resection has been the optimal treatment for most meningiomas and is meticulously performed accordingly. The patient is doing fine with no evidence of tumor recurrence on recent MR scans.